PENGARUH SENAM HIPERTENSI TERHADAP TEKANAN DARAH, FREKUENSI NADI DAN KOLESTEROL PADA KLIEN HIPERTENSI DI PUSKESMAS JABUNG SISIR PROBOLINGGO - Ulfa, Umi Mariatul (Jurnal Keperawatan Profesional, 2022)
Cardivascular disease is a disease that causes many deaths in Indonesia, one of which is hypertension. This study aims to determine the effect of hypertension exercise on blood pressure, pulse rate, and coelsterol. The kind of quantitative research with Quasi Experiment design in the form of a Pretest-Posttest Nonequivalent Control Group. The sampling technique used purposive sampling. The number of respondents in this study were 35 respondents in the intervention group and 35 respondents in the control group, which was carried out twice in 2 weeks. The results of this study indicate that in the second week systolic blood pressure there is an influence with p value (0,000) <α (0.05) while in the second week of diastolic blood pressure with p value (0,000) <α (0.05) which means there is an effect against blood pressure. In the research results, the pulse rate in the first week obtained p value (0.000) <α (0.05), which means that there is an effect of hypertension exercise on pulse. In the results of research after hypertension exercise on post cholesterol the first week and the second week there is an influence with p value (0.000) <α (0.05) which means that there is a difference in the effect of hypertension exercise on blood pressure, pulse and cholesterol in the intervention group and the control group.